ANALYSIS OF INTEREST IN ENTREPRENEURSHIP THROUGH LEARNING CREATIVE PRODUCTS IN ENTREPRENEURSHIP AND BUSINESS CENTERS FOR STUDENTS - Khoirina, Alifia Sabila; Martha, Jefry Aulia (Dharmas Education Journal (DE_Journal), 2023)
This research aims to determine students' interest in entrepreneurship through learning entrepreneurial creative products and business center activities. This research uses a qualitative approach. This type of research is phenomenological with the main informants namely students and supporting informants namely PKK teacher and business center management teacher. Data collection techniques in this research used observation and interviews. Data analysis in this research includes data collection, data reduction, data presentation and drawing conclusions. Checking the validity of the data in this research used reference materials, triangulation and increased observation persistence. The results of the research can be described as follows: Class XI BDP students have an interest in entrepreneurship and are very interested in becoming entrepreneurs after studying PKK and participating in a business center. the students thought that through PKK learning and participating in the business center program, they would train themselves to be confident in selling. Some students are interested in becoming entrepreneurs because of the interesting PKK learning and exciting business center activities. They think that being an entrepreneur is very beneficial for themselves because it will produce the best results if done in the right and diligent manner. some other students are interested in becoming entrepreneurs because of the results obtained from the sales process, this makes students want to continue selling and make a profit.